Collisions and Congestions Detection and Management in Wireless Body Sensors: A Review - Ekoro, Ekoro I.; Ogban, Usang E.; Abuo, Stephen B. (International Journal of Computing Sciences Research, 2023)
Purpose – Congestion control is a very important area within wireless sensor networks (WSN). Congestions usually occur when traffic influx becomes greater than the aggregated or individual capacity of the transmitting channels. The constrained resources of the WSN must be considered while devising such techniques to achieve the maximum throughput.  This research reviewed existing algorithms with an aim to identify the strength and weaknesses. Method – The Researchers used a survey method to identify existing works and reviews on congestions management and control in Wireless sensor Network this was done by identifying and categorizing various classes of congestion control. Conclusion – This paper present a review of most of the existing approaches and algorithms in addressing congestions. The benefits of addressing congestions are also discussed in this review paper. The paper also made suggestions for future study. Recommendation – A robust congestion checks should be implemented in wireless sensor networks to curb the level of packet drops thereby increasing network throughputs. Also hybrid algorithm that leverage on the strengths of existing algorithm should be proposed and implemented. Practical Implication – This research will not only benefit the academia, industries that implement wireless sensor network especially in healthcare will benefit tremendously from this research as the recommendations of this research will certainly aid the implementation of efficient and robust wireless network.